1994
DOI: 10.1042/bj3010211
|View full text |Cite
|
Sign up to set email alerts
|

The chondrodystrophy, nanomelia: biosynthesis and processing of the defective aggrecan precursor

Abstract: The lethal chicken mutation nanomelia leads to severe skeletal defects because of a deficiency of aggrecan, which is the largest aggregating chondroitin sulphate proteoglycan of cartilage. In previous work, we have demonstrated that nanomelic chondrocytes produce a truncated aggrecan precursor that fails to be secreted, and is apparently arrested in the endoplasmic reticulum (ER). In this study, we investigated the biosynthesis and extent of processing of the abnormal aggrecan precursor. The truncated precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Aggrecan and other proteoglycans provide a cushioning role of the matrix, but also act to immobilize and store growth factors and thereby function as molecular organizers of the ECM and cartilage in general (Rouslahti and Yamaguchi, 1991). The importance of these pathways for skeletal development is shown by several human diseases caused by mutations in the genes encoding Sox9, Collagen II, and Aggrecan, or regulators of GAG sulfation (Eyre et al, 1986;Spranger et al, 1994;Vertel et al, 1994;Wagner et al, 1994;Chan et al, 1995;Hastbacka et al, 1996;Bi et al, 2001;Rossi and Superti-Furga, 2001;Gleghorn et al, 2005).…”
Section: Chondrogenesismentioning
confidence: 99%
“…Aggrecan and other proteoglycans provide a cushioning role of the matrix, but also act to immobilize and store growth factors and thereby function as molecular organizers of the ECM and cartilage in general (Rouslahti and Yamaguchi, 1991). The importance of these pathways for skeletal development is shown by several human diseases caused by mutations in the genes encoding Sox9, Collagen II, and Aggrecan, or regulators of GAG sulfation (Eyre et al, 1986;Spranger et al, 1994;Vertel et al, 1994;Wagner et al, 1994;Chan et al, 1995;Hastbacka et al, 1996;Bi et al, 2001;Rossi and Superti-Furga, 2001;Gleghorn et al, 2005).…”
Section: Chondrogenesismentioning
confidence: 99%
“…The nanomelic chick bears a mutation in the aggrecan gene that introduces an early stop codon into the translated sequence, resulting in synthesis of a truncated core protein, which is neither glycosylated nor secreted by chondrocytes (1). The mutant precursor is modified by addition of N-linked oligosaccharides and the chondroitin sulfate chain initiating xylose, but does not acquire mature CS chains, consistent with the conclusion that it progresses no further than the endoplasmic reticulum (ER) in the secretory pathway (2). These studies suggested a previously unrecognized role for the C-terminal globular domain: that it might contain recognition or retention signals or that proper folding of this specific domain, which may involve interactions with molecular chaperones, is necessary to effect exit of the entire core protein precursor from the ER.…”
mentioning
confidence: 58%
“…From our studies, which elucidated the mutation in the nanomelic chick, it was learned that not only was there a complete lack of aggrecan in the mutant extracellular matrix, there was also an accumulation of a truncated, partially processed precursor in the chondrocyte ER, leading to the hypoth- esis that the deleted G3 domain was involved in the intracellular maturation and secretion process of this proteoglycan (1,2). In the present study, we focused mainly on: (i) identifying the minimal alteration from the native structure tolerated before aggrecan processing and secretion are affected, (ii) elucidating the pathway and players involved in the early steps of processing, (iii) investigating whether the unnatural accumulation of unprocessed core protein induces a stress-related response, and (iv) determining the mode of degradation of the ER-accumulated product.…”
Section: Discussionmentioning
confidence: 99%
“…2 H). Previous work has shown that chondrocytes derived from chickens with the nanomelic mutation synthesize a truncated form of the aggrecan protein that is not processed or secreted (Vertel et al, 1994;Domowicz et al, 1995Domowicz et al, , 1996Domowicz et al, , 2000Chen et al, 2002) and that S103L-aggrecan immunoreactivity is not observed in the notochord of nanomelic animals (Domowicz et al, 2003). Aggrecan is known to be differentially processed in different tissues (Domowicz et al, 1995), raising the possibility that neural tissue in nanomelic mutants may secrete a truncated form of aggrecan that is uniquely modified compared with chondrocytes.…”
Section: Aggrecan Expression In the Nervous Systemmentioning
confidence: 99%